Cultural stressors, identity development, and substance use attitudes among Hispanic immigrant adolescents. Issue 1 (25th October 2017) - Grigsby, Timothy J.; Forster, Myriam; Meca, Alan; Zamboanga, Byron L.; Schwartz, Seth J.; Unger, Jennifer B.
Abstract: The goal of this investigation was to determine whether various cultural stressors (bicultural stress, perceived discrimination, and perceived negative context of reception [PNCR]) predict positive and negative substance use attitudes, directly and indirectly through personal identity, in a sample of immigrant Hispanic adolescents. Data on cultural stressors, substance use attitudes, and covariates were collected from 302 Hispanic immigrant adolescents (152 from Miami [61% Cuban] and 150 from Los Angeles [70% Mexican]) at 3 time points. PNCR was associated with identity confusion (β = .175, p = .033). Identity confusion significantly predicted higher positive attitudes toward alcohol and other drug (AOD; β = .216, p < .001) and cigarette use (β = .191, p = .015) and mediated the relationship between PNCR with unfavorable AOD attitudes (β = −.019, 95% confidence interval [CI] [− 0.052,  − 0.001]) and favorable AOD attitudes (β = 0.038, 95% CI [0.003, 0.086]). Perceptions of a negative context of reception may hinder successful personal identity formation and impact health outcomes for immigrant youth.